Invasive Fungal Diseases in Africa: A Critical Literature Review - Bongomin, Felix; Ekeng, Bassey E.; Kibone, Winnie; Nsenga, Lauryn; Olum, Ronald; Itam-Eyo, Asa; Ngouanom Kuate, Marius Paulin; Pebalo Pebolo, Francis; Davies, Adeyinka A.; Manga, Musa; Ocansey, Bright; Kwizera, Richard; et al. (Journal of Fungi, 2022)
Invasive fungal diseases (IFDs) are of huge concern in resource-limited settings, particularly in Africa, due to the unavailability of diagnostic armamentarium for IFDs, thus making definitive diagnosis challenging. IFDs have non-specific systemic manifestations overlapping with more frequent illnesses, such as tuberculosis, HIV, and HIV-related opportunistic infections and malignancies. Consequently, IFDs are often undiagnosed or misdiagnosed. We critically reviewed the available literature on IFDs in Africa to provide a better understanding of their epidemiology, disease burden to guide future research and interventions. Cryptococcosis is the most encountered IFD in Africa, accounting for most of the HIV-related deaths in sub-Saharan Africa. Invasive aspergillosis, though somewhat underdiagnosed and/or misdiagnosed as tuberculosis, is increasingly being reported with a similar predilection towards people living with HIV. More cases of histoplasmosis are also being reported with recent epidemiological studies, particularly fromWestern Africa, showing high prevalence rates amongst presumptive tuberculosis patients and patients living with HIV. The burden of pneumocystis pneumonia has reduced significantly probably due to increased uptake of anti-retroviral therapy among people living with HIV both in Africa, and globally. Mucormycosis, talaromycosis, emergomycosis, blastomycosis, and coccidiomycosis have also been reported but with very few studies from the literature. The emergence of resistance to most of the available antifungal drugs in Africa is yet of huge concern as reported in other regions. IFDs in Africa is much more common than it appears and contributes significantly to morbidity and mortality. Huge investment is needed to drive awareness and fungi related research especially in diagnostics and antifungal therapy.
Keywords: invasive fungal diseases; Histoplasmosis; Cryptococcosis; Histoplasmosis; Pneumocystosis; Emergomycosis; Mucormycoses